2010
DOI: 10.1007/s11060-010-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of functional diffusion maps is a predictive imaging biomarker for cytotoxic and anti-angiogenic treatments in malignant gliomas

Abstract: Anti-angiogenic agents targeting brain tumor neovasculature may increase progression-free survival in patients with recurrent malignant gliomas. However, when these patients do recur it is not always apparent as an increase in enhancing tumor volume on MRI, which has been the standard of practice for following patients with brain tumors. Therefore alternative methods are needed to evaluate patients treated with these novel therapies. Furthermore, a method that can also provide useful information for the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…The remaining top 10 features contributing to IDH prediction were MRI features, and 8 among them were obtained by filtering tumor volumes using ADC thresholds rather than the whole tumor volumes. The utility of DWI in glioma prognostication has been demonstrated previously 20,26,43,44 ; we corroborated the utility of DWI to subselect volumes of interests with greater contribution to our model performance.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The remaining top 10 features contributing to IDH prediction were MRI features, and 8 among them were obtained by filtering tumor volumes using ADC thresholds rather than the whole tumor volumes. The utility of DWI in glioma prognostication has been demonstrated previously 20,26,43,44 ; we corroborated the utility of DWI to subselect volumes of interests with greater contribution to our model performance.…”
Section: Discussionsupporting
confidence: 84%
“…This difference has not been reported previously and could be explored on other datasets. While steroid treatment has been shown to affect the appearance of tumors by reducing contrast permeability and peritumoral edema, 20,37,38 including this feature in our model did not improve IDH prediction. The remaining top 10 features contributing to IDH prediction were MRI features, and 8 among them were obtained by filtering tumor volumes using ADC thresholds rather than the whole tumor volumes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is important to mention that many valuable biomarkers have shown the ability to predict patient survival in anti-angiogenic therapies, including [ 18 F]-fluorothymidine PET [36], dynamic contrast-enhanced (DCE)-MRI combined with blood serum markers [37], pre-treatment diffusion MR characteristics [38], conventional MR imaging characteristics [25], and functional diffusion maps (fDMs) using serial diffusion MR data [39,40]. These techniques, however, are distinctly different from the DQT2 mapping technique in that they quantify particular aspects of tumor growth, metabolism, or vasculature instead of changes in tissue T2 characteristics likely due to change in water homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Various volumetric parameters derived from the high-intensity signals on traditional MRI sequences, such CE+ T1WI, FLAIR, and T2WI, are used for brain tumor evaluation, especially volumetric changes in contrast enhancement (16)(17)(18). It has been reported that three -dimensional (3D) volumetry maybe more accurate for defining tumor volume than estimates based on 2D axial slices (19).…”
Section: Introductionmentioning
confidence: 99%